The impact of a rehabilitation program for injured ligaments and shoulder muscles and their relationship to the level of achievement of air weapons players with special needs - Ali Enad, Liqaa (International Journal of Psychosocial Rehabilitation, 2020)
The importance of research has crystallized in the development of a rehabilitation program consisting of rehabilitation exercises as well as a natural remedy (infrared) for the treatment of ligament tears and the rehabilitation of muscles working on the shoulder joint, as well as obtaining some of the necessary motor abilities such as muscle strength, accuracy, flexibility, and the appropriate motor range of the joint as it was before the injury in order to achieve the highest possible achievement and be able to make it perform optimally and return the movement of the joint naturally and in a short period of time. Relatively as much as possible, the movement of the upper limb depends mainly on the safety and effectiveness of this joint as well as the dependence of the archers mainly on it for what the effectiveness requires; either the goal of the research was in the preparation of a qualifying program and to recognize its effect using infrared and therapeutic exercises of ligaments and muscles working on the shoulder joint in the players of air weapons with special needs. The sample included (4) air-weapon gunmen 10 pistols and a 10-meter rifle from the players of ande province Baghdad with the unilateral and bilateral amputation of the lower limbs and their number (4 shooters), the category of applicants and applied the research vocabulary to the sample of the research of the shooters category emerging with air weapons (10 meters) of special needs. concluded the researcher that the rehabilitation method has an effect in improving the level of physical abilities and the level of achievement Either recommendations are the need to pay attention to the provision of modern physiotherapy methods to remedy the injury immediately after the occurrence or the use of preventive and therapeutic means to avoid injury as much as possible.